The History of N.V. Nederlandsch-Indische Gas-Maatschappij in Medan (1919-1950) - Rahma, Aisyah Zalfaa Ar; Ginting, Junita Setiana; Junaidi (Siginjai: Jurnal Sejarah, 2026)
This research examines the history of the Nederlandsch-Indische Gas-Maatschappij (NIGM) in Medan between 1919 and 1950. The focus of this study is to explore various important aspects of NIGM and its development in Medan during that period. NIGM was a private institution that played a significant role in the commercialization of gas and electricity in the Dutch East Indies. The main focus of this research is to trace the development of NIGM’s activities in the municipality Gemeente of Medan, including the process of concession applications, the expansion of company units, and the evolution of its marketing strategies. The primary objective of the study is to follow the company’s trajectory in Medan and its surrounding areas, from the initial concession period to 1950, when the company was renamed Gas-Overzeese Maatschappij (OGEM). This study employs the historical method with a chronological approach, drawing on primary sources such as company archives, NIGM’s annual reports, and colonial government regulations. The findings show that NIGM was a major company that commercialized gas and electricity for both the government and the public in Medan. Initially, NIGM succeeded as a lighting provider in Batavia at the end of the 19th century. It later expanded its concessions to nearby cities and eventually to Medan and its surroundings. However, the company’s expansion was not without challenges, including conflicts of interest with local authorities as well as technical and economic difficulties. The study concludes that NIGM’s history forms an essential part of the long development of electrification and modernization in the Dutch East Indies, particularly in Medan—a legacy that persists to this day. The company serves as a representation of how colonial private enterprises contributed to shaping the urban landscape and daily life during the late colonial era.